Correlation Between the Ratio TG/HDL-C and Lipid Profile in Nonalcoholic Fatty Liver Disease Patients - Siregar, Hafiz Syaifullah; M.Aron Pase (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Background: Insulin resistance is identified as an impaired biological response to insulin stimulation of target tissues primarily in the liver, muscle, and adipose tissue. The ratio TG/HDL-C has been proposed as a simple marker of insulin resistance. The study aimed to determine the correlation between the ratio TG/HDL-C and lipid profile in nonalcoholic fatty liver disease (NAFLD) patients Method: The design of the study was a cross-sectional study with the dependent variable Fibrosis Score of NAFLD sufferers who came to H. Adam Malik Medan General Hospital network hospital from July-September 2021. Diagnosis of NAFLD from anamnesis, physical examination, laboratory, and abdominal ultrasound. Lipid profile examination is carried out using a spectrophotometer tool colorimetric enzymatic method, observed include TC, HDL-C, LDL-C, and TG. Results: There are 80 NAFLD patients, aged 54.8±8.7 years, with uncontrol T2DM, and normal weight. There was a correlation significantly between the ratio TG/HDL-C with TC-C, TG, HDL-C, LDL-C (p<0.001), and no correlation between ratio TG/HDL-C with age, BMI, FPG, PPG, and HbA1c (p>0.05) Conclusion: There is a correlation between ratio TG/HDL-C (as a marker of insulin resistance) and lipid profile in NAFLD patients